Histoplasmosis prevalence among medical students of the faculty of Medicine Islamic University of North Sumatera and the association between pet animal and histoplasmin test. - Azhar Tanjung, Azhar Tanjung (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1997)
A cross sectional study was conducted at the Faculty of Medicine, Islamic University of North Sumatera (FK MU) Medan with the population of 169 medical students. It was found that the prevalence of histoplasmosis was 13.61% and there was no correlation between the gender with the histoplasmin test reactivity. The most precipitating factor of the prevalence for the positive histoplasmin test was pet animal. The other precipitating factors were found such as in bat, cave adventure and contact with wood environment. There was significant association between pet animal and the reactivity of histoplasmin test. In conclusion, the prevalence of histoplasmosis with moderate category is found in the young adult population group. The pet animal has significant possibility as the precipitating factors and its role is needed for further attention.Key words : histoplasmosis - histoplasmin test - prevalence - young adult - pet animal.